Whatsapp Use Behaviour in Relation to Social Interaction Anxiety and Personality among Students - George, Ansiem; S. Preetha, Dr; Pramod S. K, Dr (International Journal of Engineering and Technology, 2018)
WhatsApp is a trendy application that is widely used as a medium of communication all around the world. Student community uses it for communication, social interaction and learning purposes. Inappropriate use of WhatsApp results in addictive behavioural patterns that require authentic attention from parents, teachers and even from mental health care professionals. Personality, social anxiety, and lack of real time communication sources tempt students to use WhatsApp more than what is expected. The present study focused on â€œWhatsApp Use Behavior in relation to social interaction anxiety and personality among studentsâ€. The sample(N=120) comprising of both male (52) and female (68) school and college students in the age range of 15-24 years, were selected conveniently from SSLC, PlusTwo, Degree and Post Graduate levels. WhatsApp Use Behavior Scale, Social Interaction Anxiety Scale and Big Five Personality Inventory were administered to collect the necessary data from the sample. Result revealed statistically significant relationship between the WhatsApp Use Behavior and Social Interaction Anxiety and Personality among students.13 % of the participants use WhatsApp at a very high level that is seemingly addictive in nature. There exists a significant positive low correlation between WhatsApp Use Behavior and Social Interaction Anxiety and there exists no significant correlation between WhatsApp Use Behavior and extroversion- introversion dimension of personality. They are usually driven by the thoughts of WhatsApp use and they spent most of the time in using WhatsApp and their daily routines are often affected by this behavior. Each day the WhatsApp use craze among students seems to increase. Many students get driven out by the extensive use of WhatsApp and are not able to focus on their studies. The t- test result indicates a significant difference between males and females in their WhatsApp Use behavior. Males are having high level of WhatsApp Use Behavior than females.Â  ANOVA results indicate that there exists a significant difference among students in their WhatsApp Use Behaviour on the basis of education and age. There exists no significant difference among students in WhatsApp Use Behavior on the basis of Personality (Extraversion â€“ introversion Dimension). The study also suggests that students should be aware of theÂ  addictive behavioral patterns of WhatsApp and its consequences.Â